PERTANGGUNGJAWABAN KORPORASI DALAM TINDAK PIDANA KORUPSI DI SEKTOR PERTAMBANGAN ILEGAL - Melsi Arosty; Yudi Krismen (STKIP Subang, 2026)
This study examines corporate criminal liability in corruption cases within the illegal mining sector in Indonesia. The research employs a normative juridical method with statutory and conceptual approaches. Data were collected through literature review and analyzed qualitatively. The findings reveal that corporations can be held criminally liable for corruption in illegal mining activities based on Law No. 31 of 1999 jo. Law No. 20 of 2001 on Eradication of Corruption Crimes and Law No. 3 of 2020 on Mineral and Coal Mining. However, enforcement faces challenges including evidentiary difficulties, the principle of ultra vires, and the complexity of corporate structures. The study recommends strengthening the legal framework, enhancing inter-agency coordination, and implementing strict liability principles for corporations in environmental crimes.